Advances in the development of universal influenza vaccines. Issue 5 (24th September 2012) - Gilbert, Sarah C.
<x xml:space="preserve">Abstract</x> Please cite this paper as: Sarah C. Gilbert. (2012) Advances in the development of universal influenza vaccines. Influenza and Other Respiratory Viruses DOI:10.1111/irv.12013. Despite the widespread availability and use of influenza vaccines, influenza still poses a considerable threat to public health. Vaccines against seasonal influenza do not offer protection against pandemic viruses, and vaccine efficacy against seasonal viruses is reduced in seasons when the vaccine composition is not a good match for the predominant circulating viruses. Vaccine efficacy is also reduced in older adults, who are one of the main target groups for vaccination. The continual threat of pandemic influenza, with the known potential for rapid spread around the world and high mortality rates, has prompted researchers to develop a number of novel approaches to providing immunity to this virus, focusing on target antigens which are highly conserved between different influenza A virus subtypes. Several of these have now been taken into clinical development, and this review discusses the progress that has been made, as well as considering the requirements for licensing these new vaccines and how they might be used in the future.